Heterologous expression of bacterial natural product biosynthetic gene clusters - Wuisan, Zerlina Gabriela; Justus Liebig University Giessen (My University, 2021)
Antimicrobial resistance (AMR) has been declared as a global threat by the United Nations (UN). Therefore, it is of an utmost importance to find novel bioactive compounds that could be developed into a drug lead. As the conventional antibiotic discovery pipeline dried up, a synthetic biology-based strategy has become a promising alternative, due to the advances in sequencing technology. The strategy includes genome mining to detect putative biosynthetic gene clusters (BGCs), genetic engineering (e.g. to add promoters) and cloning of the BGCs into expression vectors, and heterologous expression to identify compounds that are produced by the BGCs. This strategy is advantageous to obtain novel compounds from cryptic or silent BGCs, as well as to prove the link between a BGC and a compound of interest. This study is separated into two main parts: Chapter III: Heterologous expression of non-ribosomal peptide synthetase (NRPS) and polyketide synthase (PKS) BGCs and Chapter IV: Heterologous expression of ribosomally synthesized and post-translationally modified peptide (RiPP) BGCs. In Chapter III, the genomic DNA of bioactive understudied bacteria from unusual sources, i.e. the egg mass of marine slugs and the gut of burying beetles, were analysed in silico for putative NRPS and PKS BGCs. The putative BGCs were successfully cloned into expression vectors, and synthetic promoters were inserted. Then, the integrative vectors that carry the respective putative BGCs were introduced into different Streptomyces heterologous expression hosts. Although the heterologous expression of the BGCs did not result in the detection of natural products (NPs) that could be linked to the respective BGC, the methods applied and discussed here were proven to be efficient in capturing of large BGCs from Actinobacteria. Moreover, the constructs that were generated can be used as the basis for future studies. The prospective work to improve the heterologous expression of NP BGCs is discussed in section III.4.3. In Chapter IV, the heterologous expression of a RiPP BGC was aimed to link it to a compound of interest, i.e. darobactin A. Additionally, the minimal BGC to produce darobactin A was determined and the heterologous expression system was optimized to increase production yield and decrease fermentation period to ensure compound supply for future animal studies. The heterologous expression system developed in this study has become the basis for the heterologous expression of natural darobactin analogs, marine-derived darobactins, and the bioengineering of derivatives libraries. In conclusion, the synthetic biology-based approach for the discovery of novel antibiotics is an advancing field. The tools for better BGC prediction are continuously being perfected and with the bioinformatic tools that are now available, putative BGCs could be predicted, unveiling the potential of NP discovery from understudied bacteria. The generation of a defined metagenomic library as the DNA source for capturing target BGCs was proven to increase TAR cloning efficiency up to 92.8%. However, the optimization of the heterologous system is necessary for a successful biosynthesis, especially for the heterologous expression of NP BGCs from understudied bacteria. In contrast, the heterologous expression of BGCs from well-studied bacteria of the genus Photorhabdus in the comprehensively studied host Escherichia coli has proven the functionality of the darobactin A BGC.
Keywords: Natural Products; Heterologous expression; RiPP; NRPS; Genetic engineering; ddc:570